An illustrated catalogue of the scalpellid barnacles (Crustacea: Cirripedia: Scalpellidae) collected during the HMS “Challenger” expedition and deposited in the Natural History Museum, London - Shalaeva, Kate (Zootaxa, 2014)
For the first time since 1883, the “Challenger” collection of scalpellids stored in the Natural History Museum (London) and studied by Hoek, has been reviewed. It comprises 40 species now assigned to 17 genera and three subfamilies within the family Scalpellidae. A checklist of published records, type status, sources of supplementary descriptive information, updated distributions and known depth records is given. New photographs are included which may be useful for species identification and for any future systematic rearrangement of the scalpellids. Trianguloscalpellum weltnerianum (Pilsbry, 1911) is recognised as a junior subjective synonym of Trianguloscalpellum album (Hoek, 1883).